Psychological well-being of the community during the Covid-19 pandemic - Nur Ramadhani; Ismiyati Yuliatun; Tarmilia; Kumaidi (Urecol Journal. Part H: Social, Art, and Humanities, 2021)
The Covid-19 pandemic triggers the emergence of pressure, anxiety, fear and other psychological disorders that can disrupt the psychological well-being of the community. This study aims to determine the psychological well-being of the Boyolali society during the Covid-19 pandemic. The research sample is the society of Boyolali Regency aged 18 years and over. As many as 271 people obtained by quota sampling with inclusion criteria. Data collection was carried out using the Society Psychological Wellbeing instrument. The results of the validity test obtained 49 valid items and 7 dropped items. The reliability test of this instrument is 0.921, meaning that this instrument has high reliability and can be trusted. The data were then analyzed descriptively. The results showed that the society had a high level of welfare of 27%, a medium level of 72%, and a low level of 2%. The environmental mastery dimension in the medium category gets the lowest percentage of 46.5%. Conclusion: the psychological well-being of the society during the Covid-19 pandemic in this study was mostly at a moderate level, then high and low levels. People with high and moderate levels of psychological well-being need efforts to maintain the psychological well-being they already have.